2012
DOI: 10.1002/lary.23506
|View full text |Cite
|
Sign up to set email alerts
|

A trial of drug‐induced sleep endoscopy in the surgical management of sleep‐disordered breathing

Abstract: Drug-induced sleep endoscopy provides more clinical information to assess airway function and collapse than awake endoscopy alone and assists in the surgical planning. Additional investigation is needed to standardize drug-induced sleep endoscopy techniques, training, and interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 17 publications
3
72
1
6
Order By: Relevance
“…Test---retest reliability was good (K = 0.61). 18 The inter-rater reliability was also observed by Kezirian et al in a prospective study of 108 patients, in which all subjects exhibited evidence of palatal obstruction and most also demonstrated hypopharyngeal obstruction. Both reviewers determined that most individuals had palate and hypopharynx obstruction.…”
Section: Kezirian Et Al 11mentioning
confidence: 63%
“…Test---retest reliability was good (K = 0.61). 18 The inter-rater reliability was also observed by Kezirian et al in a prospective study of 108 patients, in which all subjects exhibited evidence of palatal obstruction and most also demonstrated hypopharyngeal obstruction. Both reviewers determined that most individuals had palate and hypopharynx obstruction.…”
Section: Kezirian Et Al 11mentioning
confidence: 63%
“…Slow stepwise induction is required to avoid oversedation. Recently, bispectral index monitoring (BIS) during DISE has been introduced to determine the level of sedation required for assessment of snoring and/or obstruction [28,32]. Once the patient has reached a satisfactory level of sedation, a flexible endoscope is introduced into the nasal cavity.…”
Section: Dise: Sedation Methods Contraindications and Complicationsmentioning
confidence: 99%
“…In Friedman I and II tongue positions [39] the greatest difference was found (DISE 88.9 %, OPDA 16.7 %). Gillespie et al [32] prospectively studied a group of 38 patients and found a change in surgical plan after DISE in 23 (62 %) patients compared to awake endoscopy. A high ASA (C3) score and propofol or midazolam allergies (albeit rare) are considered contraindications.…”
Section: Dise: Sedation Methods Contraindications and Complicationsmentioning
confidence: 99%
“…[7][8][9] Evidence is emerging that certain DISE findings are related to treatment outcome and that DISE is a valuable selection tool in treatment decision-making. [10][11][12][13][14][15] Approximately 100 articles have been published on DISE just in the last 5 years. The recently published European position paper provides a comprehensive review and starting point for the reader interested in more in-depth analysis of the data and controversies surrounding DISE.…”
Section: Novel Diagnostic Evaluation Approachmentioning
confidence: 99%